Flexible Nail Treatment of Pediatric Both-Bone Forearm Fractures. (August 2022) - Spahn, Kimberly M.; Pring, Maya; Collier, Martin
Summary: Although most pediatric both-bone forearm fractures are treated nonoperatively, some do require surgical fixation. This article and accompanying step-by-step technique video demonstrate intramedullary fixation of a both-bone forearm fractures in a 7-year-old boy.